KOSMOLOGI IBN SINA: LANDASAN FILOSOFIS DAN EPISTEMOLOGIS BAGI ILMU PENGETAHUAN ISLAM MODERN - Vici Ramananda; efendi efendi; Gazali Gazali (Universitas Islam Negeri Imam Bonjol Padang, 2026)
This study examines Ibn Sina's cosmology as a philosophical and epistemological foundation for modern Islamic scholarship, using qualitative library research grounded in Gadamerian hermeneutics, particularly the concept of fusion of horizons. Three interrelated dimensions are analyzed. First, at the philosophical level, Ibn Sina's proof of God through Necessary Being (Wajib al-Wujud) and Contingent Being (Mumkin al-Wujud) is shown to systematize, rather than merely extend, al-Farabi's earlier framework, though its validity depends on the unproven axiom that causal regress cannot be infinite. Second, at the epistemological level, Ibn Sina's theory of knowledge mirrors his cosmological structure: the graded stages of human intellect depend on humanity's position within the hierarchy of emanation, culminating in a reading of the sublunar world's ontological fragility, governed by the Tenth Intellect, as structurally analogous to entropy in modern thermodynamics. Third, regarding relevance to modern scholarship, Ibn Sina's framework can be cautiously engaged with select contemporary questions, including fine-tuning, the anthropic principle, and Wheeler's